Burlesque West: Showgirls, Sex and Sin in Postwar Vancouver - Hunt, Gerald (Labour / Le Travail, 2011)
The article reviews the book, "Burlesque West: Showgirls, Sex and Sin in Postwar Vancouver," by Becki Ross.
Keywords: BOOKS -- Reviews; BURLESQUE West: Showgirls, Sex & Sin in Postwar Vancouver (Book); Nonfiction; PROSTITUTION -- History; ROSS, Becki